Pregnancy and undifferentiated connective tissue disease: outcome and risk of flare in 100 pregnancies. (8th October 2019) - Zucchi, Dina; Tani, Chiara; Monacci, Francesca; Elefante, Elena; Carli, Linda; Parma, Alice; Stagnaro, Chiara; Ferro, Francesco; Gori, Sabrina; Strigini, Francesca Anna Letizia; Mosca, Marta
Abstract: Objective: UCTD is a systemic autoimmune condition that fails to fulfil the criteria for a definite CTD. Given that there are a lack of studies on links between pregnancy and UCTD, the purpose of this study was to evaluate the risk of disease flares or development of CTD in addition to the risk of adverse pregnancy outcomes in patients with UCTD. Methods: This is a retrospective study using prospectively collected data for 100 pregnancies in 81 incidences of UCTD treated in a single referral centre. Results: A total of 11 pregnancies (11%) ended in miscarriage in the first trimester and the remaining 89 (89%) ended with a live birth. Thirteen patients (13%) flared during pregnancy or puerperium and three (3%) suffered major flares that led to the development of SLE with renal involvement. Obstetric complications occurred in 26 of the 89 successful pregnancies (29%), including 1 case (1%) of pre-eclampsia; in some cases, a single pregnancy was affected by more than one complication. There was a significant link between disease flare and both anti-dsDNA-positive antibodies at baseline ( P < 0.01) and disease activity at the beginning of pregnancy ( P < 0.01). Conclusion: The impact on pregnancy in the study's cohort appears to be less serious in UCTD than in other CTDs. Nevertheless, disease flares and obstetric complications can represent a clinical challenge and clinical and serological disease activity would appear to represent important determinants of pregnancy outcomes. Pre-pregnancy counselling and planning as well as close monitoring during pregnancy is therefore essential.